The Alternate Modes of Transportation in International Logistics - Babu, B. Mariappa; Aithal, P.S. (Apex Journal of Business and Management, 2023)
To study the need for alternate modes of transportation in international logistics in general. To analyse the constraints posed by Indian ports and to evaluate the existing modes of transportation other than major ports. To assess the need for an alternative mode of transportation. To discuss the emerging alternate modes of transportation that are in the pipeline. An exploratory research design is used in the research study. A comprehensive literature review of existing literature, such as the Ministry of Shipping in India or port authorities, for the most accurate and up-to-date information on the utilization of capacity in Indian ports, as the latest data on port capacity utilization can provide references or reports to support the claim. Additionally, to review industry reports or publications which may provide insights into the utilization levels of Indian ports. To analyse data released by the Ministry of Commerce, the Director General of Foreign Trade, and the Ministry of Ports, Shipping and Waterways. To analyse logistics and transportation-related journals & newspaper articles relating to emerging transportation. Sea transport through major ports has almost reached its full capacity, air transport though fast is expensive, rail transportation is slow, and road transportation, though offers door-to-door service is unreliable. Further, Indian ports have to overcome 2 main constraints, namely the Port and Vessel Constraints. The recent changes in the international logistics sector include Skylon, Space Elevator, Rope Cars, Metrino Butt, Hyperloop, and UR Air Vehicle. Space ay and Ground Way are viable modes of transportation, but the cost and research interest may delay them. A exploratory study to understand the issues in Indian ports, to analyse the need for other modes of transportation such as air, road, outer harbour, inland water connectivity, etc, and to explore the other modes of transportation that are in the pipeline and at the research stage.